2022
DOI: 10.3390/molecules28010026
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Characterization, Antioxidant and Anti-Inflammatory Effects of Cleome arabica L. Fruits Extract against Formalin Induced Chronic Inflammation in Female Wistar Rat: Biochemical, Histological, and In Silico Studies

Abstract: In recent decades, the use of herbs and plants has been of great interest, as they have been the sources of natural products, commonly named as bioactive compounds. In specific, the natural compounds from the Capparaceae family which has been proved to have antioxidant, anti-inflammatory, antimicrobial and anti-carcinogenic activities, by several studies. Cleome arabica L. (CA) specie is the most used medicinal plants in Tunisia and elsewhere in North African countries for treatment of various diseases includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 81 publications
1
4
0
Order By: Relevance
“…The phenolic compounds especially flavonoids are endowed of the antioxidant activity (Nair and Gupta, 1996;Costa et al, 2012). Other studies have indicated that alkaloids, flavonoids, phenols and tannins are responsible for the antioxidant potential of medicinal plants (Allagui et al, 2023). These plants' chemicals have been found in substantial quantities in S. verticulatta in our experiments in this research work.…”
Section: Antioxidant Testsupporting
confidence: 55%
“…The phenolic compounds especially flavonoids are endowed of the antioxidant activity (Nair and Gupta, 1996;Costa et al, 2012). Other studies have indicated that alkaloids, flavonoids, phenols and tannins are responsible for the antioxidant potential of medicinal plants (Allagui et al, 2023). These plants' chemicals have been found in substantial quantities in S. verticulatta in our experiments in this research work.…”
Section: Antioxidant Testsupporting
confidence: 55%
“…The increasing prevalence of this phenomenon emphasizes the importance of natural antioxidants, namely those found in extracts of plants. The key active ingredients responsible for the antioxidant activity have been identified as polyphenolic chemicals, specifically tannins and flavonoids [ 56 , 57 ]. The aforementioned findings emphasize the importance of investigating antioxidants derived from plants as a means of discovering alternative sources that are both natural and beneficial for human health.…”
Section: Resultsmentioning
confidence: 99%
“…While, inflammatory phase create from 20 to 60th min after formalin injection ( Dehkordi et al, 2019 ). The acute phase is because of activation of nociceptors, while the chronic stage is an inflammatory response ( Kumar and Vinayak, 2020 , Jha et al, 2013 , Allagui et al, 2022 ). By the way, evidences have demonestrated that attenuation of the inflammatory response led to antinociceptive effects in formalin test ( Allagui et al, 2022 , Gwon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The acute phase is because of activation of nociceptors, while the chronic stage is an inflammatory response ( Kumar and Vinayak, 2020 , Jha et al, 2013 , Allagui et al, 2022 ). By the way, evidences have demonestrated that attenuation of the inflammatory response led to antinociceptive effects in formalin test ( Allagui et al, 2022 , Gwon et al, 2021 ). Previous studies have reported a key role for oxidative stress in the pathophysiology of pain in formalin test ( Basit et al, 2022 , Kiasalari et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%